2017
DOI: 10.1039/c7nj02900d
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic and molecular dynamics simulation approach towards the stabilizing effect of ammonium-based ionic liquids on bovine serum albumin

Abstract: Experimental and theoretical evidence in support of the stabilizing effect of ammonium-based ionic liquids on thermal unfolding/refolding of bovine serum albumin is provided in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The intrinsic fluctuations present in the BSA backbone in the aqueous system are in agreement with the previous study. 52 Domain I and III of BSA are more flexible in comparison to domain II. The addition of reline in water induces enhanced fluctuations at both the studied concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic fluctuations present in the BSA backbone in the aqueous system are in agreement with the previous study. 52 Domain I and III of BSA are more flexible in comparison to domain II. The addition of reline in water induces enhanced fluctuations at both the studied concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The Tyr‐411, Lys‐413, and Lys‐414 amino acid residues of BSA are located in site II (subdomain IIIA), have catalytic cleavage mechanisms, and contribute in esterase‐like activity of BSA. Tyr‐411 is the first amino acid residue of BSA which rapidly acetylated by PNPA . In this respect, the binding sites of drugs with the substrate (PNPA) are closely related to inhibition of drugs on major esterase‐like activities of BSA.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking is a modern analysis tool for scientific research to validate the ligand and protein interaction; hence, molecular docking has been performed to study the precise binding modes of 4MMC on BSA by using the AutoDock 4.2 . The probable conformations of the 4MMC and BSA complex were considered by using AutoDock program.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to experimental approaches for evaluating the effect on ILs on the protein stability, various in silico analyses have also been performed. For instance, a study using molecular dynamics simulation analysis indicated that in the presence of ILs the bovine serum albumin does not destabilize the structure it adopts, which was also confirmed by experimental analysis [ 206 ]. These molecular dynamics simulations will undoubtedly help to narrow the field of potential IL candidates for specific protein and biomolecular applications.…”
Section: Conclusion/perspectivementioning
confidence: 81%